The Effect of Content Marketing and Personal Selling on Purchase Intention at Roti Romi Medan - Nindya Yunita; Ahmad Fadlan (Lembaga Riset dan Inovasi Al-Matani, 2023)
ABSTRACT The development of digital technology, which is currently increasing rapidly, provides many conveniences that provide new opportunities in various aspects, especially in world marketing. One of the uses of technology that can be used by businesses to market their products is the use of social media. This study aims to determine the effect of using social media using content marketing and personal selling on purchase intentions at Roti Romi Medan. The type of research used is descriptive quantitative research and the nature of this research is explanatory research. The sampling technique in this study is a non-probability sampling technique. Sampling was done by accidental sampling, namely as many as 99 respondents. Data were analyzed with SPSS. The results of the study prove that content marketing and personal selling both partially and simultaneously have a positive and significant effect on purchase intention.